What do we work for? An anatomy of pre- and post-tax earnings growth - Anders Frederiksen; Timothy Halliday; Alexander K. Koch (Institute for the Study of Labor (IZA), 2010)
Promotions and cross-firm mobility provide substantial gains in earnings - a well established finding based on gross income data. Yet, what matters for incentives is how much an individual can consume or save after taxation. We show that net and gross income growth patterns may differ substantially when a progressive tax system allows for deduction opportunities. Exploiting unique matched employer-employee data with information on tax payments and employee mobility, we find that gross income gains from promotions and cross-firm mobility do not translate into significantly higher net income growth, because employees adjust their tax-shielded consumption and savings (in particular, deductible private pension contributions and mortgage-financed housing) to maintain constant net income growth.
Keywords: M51; J6; C33; H31; 330; earnings growth; promotions; mobility; taxable income; dynamic panel data models; matched employer-employee data; Einkommen; Erwerbsverlauf; Arbeitsmobilität; Einkommensteuer; Steuerprogression; Steuerbelastung; Verfügbares Einkommen; Dänemark